PENYELIDIKAN SIFAT MEKANIS BAHAN KOMPOSIT POLIMER DIPERKUAT SERAT BATANG PISANG KEPOK AKIBAT BEBAN IMPACT - surya hadi; ade irwan; Fadly Ahmad (Universitas Harapan Medan, 2020)
Banana stem fiber is a tipe of fiber with good strength and alternative material that can be used as a resforcing material in the manufacture of composit.the use of banana fiber as a composit material is an alternative in making scientific composit. The research aims to determine the effect of variation in the volume fraction of banana fiber on the strength of impact.